Prevalence of canine transmigration: Introducing a novel classification for mandibular canine transmigration - Mahitha Mohan; S. Babukuttan Pillai; G. Sreejith Kumar (Journal of Orthodontic Science, 2025)
OBJECTIVE: The aim of this study was to evaluate the prevalence of canine transmigration and impaction among patients at a tertiary dental health care center in India, using panoramic radiographs, and to introduce a novel classification system for mandibular canine transmigration. MATERIALS AND METHODS: A retrospective analysis of digital orthopantomograms (OPGs) of 30,000 patients above the age of 12 years, obtained from a tertiary dental health care center was conducted to assess the prevalence of canine transmigration and canine impaction. RESULTS: A total of 30,000 OPGs were examined, revealing 341 transmigrated canines, with an overall prevalence of 1.1%. Transmigration was more common in the mandible (246 canines, 0.8%) than in the maxilla (95 canines, 0.3%), and slightly more prevalent in females, though not statistically significant. In the mandible, 235 cases were unilateral and 11 were bilateral. All maxillary cases were unilateral. The 246 transmigrated mandibular canines were categorized using the new MBS classification system: Group I (117), Group II (100), Group III (16), Group IV (2), and Group V (11). CONCLUSIONS: Canine impaction was more prevalent in the maxilla, whereas transmigration was more prevalent in the mandible. The MBS classification system showed the highest prevalence in Group I (oblique), followed by Group II, with the lowest in Groups III (vertical) and Group IV. This system provides a more detailed and clinically useful framework than previous classifications.